Analisa Yuridis Perlindungan Hukum Pelaku Usaha Perdagangan Gas Industri Sehubungan Pinjam Pakai Tabung Gas Berdasarkan Hukum Perlindungan Konsumen (Studi Putusan Pengadilan Negeri Cibinong Nomor 84/Pdt.G/2022/PN.Cbi) - Malvin Santoso (CV Rewang Rencang, 2024)
This research aims to explain the forms of legal protection that can be pursued by entrepreneurs if they suffer losses to their legal rights as stipulated in Article 6 of the Consumer Protection Law (UUPK). This study will take the perspective of the Cibinong District Court Decision Number 84/Pdt.G/2022/PN.Cbi to find a more relevant intersection concerning the standard agreements used as a fundamental basis in legal relations involving the sale and purchase of gas and the borrowing of gas cylinder containers. The results of the study indicate that the UUPK does not yet provide comprehensive sanctions to restore the rights of the harmed entrepreneurs.